Cryptic purine transporters in Aspergillus nidulans reveal the role of specific residues in the evolution of specificity in the NCS1 family. - Sioupouli, Georgia; Lambrinidis, George; Mikros, Emmanuel; Amillis, Sotiris; Diallinas, George (Mol Microbiol, 2017)
NCS1 proteins are H(+) or Na(+) symporters responsible for the uptake of purines, pyrimidines or related metabolites in bacteria, fungi and some plants. Fungal NCS1 are classified into two evolutionary and structurally distinct subfamilies, known as Fur- and Fcy-like transporters. These subfamilies have expanded and functionally diversified by gene duplications. The Fur subfamily of the model fungus Aspergillus nidulans includes both major and cryptic transporters specific for uracil, 5-fluorouracil, allantoin or/and uric acid. Here we functionally analyse all four A. nidulans Fcy transporters (FcyA, FcyC, FcyD and FcyE) with previously unknown function. Our analysis shows that FcyD is moderate-affinity, low-capacity, highly specific adenine transporter, whereas FcyE contributes to 8-azaguanine uptake. Mutational analysis of FcyD, supported by homology modelling and substrate docking, shows that two variably conserved residues (Leu356 and Ser359) in transmembrane segment 8 (TMS8) are critical for transport kinetics and specificity differences among Fcy transporters, while two conserved residues (Phe167 and Ser171) in TMS3 are also important for function. Importantly, mutation S359N converts FcyD to a promiscuous nucleobase transporter capable of recognizing adenine, xanthine and several nucleobase analogues. Our results reveal the importance of specific residues in the functional evolution of NCS1 transporters.